2006
DOI: 10.1016/j.procbio.2006.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Production and modification of bioactive biosurfactants

Abstract: The soil bacterium Tsukamurella spec. DSM 44370 produces a mixture of oligosaccharide lipids when cultivated on sunflower oil. In contrast cultivation with calendula oil as carbon source afforded a different product composition with overproduction of 2,3-di-O-acyl-ß-Dglucopyranosyl-(1-2)-ß-D-galactopyranosyl-(1-6)-4,6-di-O-acyl-α-D-glucopyranosyl-(1-1)-α-Dglucopyranose (GL 3) that amounted to 60 % of the whole product. GL3 and its parent tetrahexose backbone G 3 were then modified enzymatically with the lipase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…These compounds can be synthesized by microorganisms growing on water-immiscible hydrocarbons, as well as on water-soluble compounds such as glucose, sucrose, glycerol, or ethanol, and can be excreted or remain attached to the cell wall [5]. Diversity existing among the biosurfactant-producing microorganisms suggests that their production represents an important survival strategy and appears to have evolved in an independent, yet parallel fashion [6,7]. A number of studies have reported the potential of lactobacilli as biosurfactantproducers [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds can be synthesized by microorganisms growing on water-immiscible hydrocarbons, as well as on water-soluble compounds such as glucose, sucrose, glycerol, or ethanol, and can be excreted or remain attached to the cell wall [5]. Diversity existing among the biosurfactant-producing microorganisms suggests that their production represents an important survival strategy and appears to have evolved in an independent, yet parallel fashion [6,7]. A number of studies have reported the potential of lactobacilli as biosurfactantproducers [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with chemical surfactants, these compounds have several advantages such as lower toxicity, higher biodegradability, and effectiveness at extreme temperatures and pH values [2,4,5]. Moreover, biosurfactants can be tailor-made to suit different applications by changing the production conditions, or by modifying the genes involved in their biosynthesis [5,7]. The diversity of biosurfactants makes them an attractive group of compounds for use in a wide variety of industrial and biotechnological applications such as agriculture, food production, chemistry, cosmetics, and pharmaceutics [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on studies on the acylation of the microbial oligosaccharide lipid GL3 (from Tsukamurella sp.) using oleic acid, the lipase Novozym 435, the solvent MTBE and a molecular sieve at 55°C 24, all lipase‐catalyzed reactions were initially performed. Later on the solvent and temperature had to be adapted to the solubilization behavior of educts.…”
Section: Resultsmentioning
confidence: 99%
“…Comparable results we obtained using diglucosyl gly cerolipids from a marine sponge-associated Bacillus pumilus strain and, additionally, using diand tetrasaccharide lipids produced by the soil bacterium Tsukamurella sp. (Ramm et al, 2004;Langer et al, 2006).…”
Section: Short-term In Vitro Bioassay For Antitumour Promotersmentioning
confidence: 99%